Perovskite device efficiency is a poor predictor for the number of citations a paper will get. (7th November 2022) - Maqsood, Ayman; Jacobsson, T. Jesper
Abstract : Beeswarm plot for over 7000 papers with original perovskite solar cell data, where the area of the circles corresponds to the number of citations the papers had obtained by 2022-03-26 and the colour reflects the top device efficiency in each paper. Abstract : One of the most common metrics of success for a perovskite solar cell is the device efficiency. Other metrics, like long-term stability and price, are also vital for commercialisation, but it is the increase in device efficiencies that has given the halide perovskites their place in the spotlight. From an academic perspective, another important metric is a paper's number of citations. That may be a flawed measure of a paper's importance but, for better or worse, it is used as a key indicator in evaluations and is thus of in-universe academic importance. A recurrent theme in perovskite research has been a race towards higher solar cell efficiency, and a common sentiment has been that efficiencies must be high for the work to be taken seriously and for it to attract citations. This paper looks closer at that assumption by analysing citation data, as a comparative measure of success, with respect to device efficiencies extracted from the Perovskite Database Project. An analysis of 7330 papers reporting original device data shows that except for papers that report record, or close to record, PCE-values, the device efficiency has little effect on the number of citations. Except for top papers, the device efficiency has close to zero predictive power with respect to the number of citations. The PCE-values are also only weakly linked to the journal impact factor. The device experimentalist can thus rest assured that unless top class efficiencies are near, the perovskite community will, on average, see beyond the device efficiencies and recognise the work for its other qualities. An increased focus on the core message may thus be more valuable with a better impact payoff than an intense optimisation endeavour increasing the efficiency with one or two more percent units.